Effect of cross-linking agent on the characteristics of celecoxib loaded chitosan microspheres - Thakkar, Hetal Paresh; Murthy, Rayasa Ramachandra (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of the present investigation was to compare the characteristics of the microspheres of chitosan prepared using two different cross-linking agents: viz. formaldehyde and glutaraldehyde and by simple heat treatment. Chitosan microspheres were prepared by emulsification cross-linking method. Microspheres were characterized for entrapment efficiency, particle size, in-vitro drug release and surface morphology was studied by scanning electron microscopy. The entrapment efficiency of the glutaraldehyde and formaldehyde cross-linked microspheres was significantly higher (P<0.05) than the heat-cross-linked microspheres. In-vitro drug release studies indicated that the microspheres cross-linked using glutaraldehyde showed slower release rate than those cross-linked with formaldehyde while the heat cross-linked microspheres showed the fastest release.